2015
DOI: 10.1016/j.ultrasmedbio.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

VEGFR2-Targeted Contrast-Enhanced Ultrasound to Distinguish between Two Anti-Angiogenic Treatments

Abstract: The aim of this study was to evaluate the capacity of BR55, an ultrasound contrast agent specifically targeting vascular endothelial growth factor receptor 2 (VEGFR2), to distinguish the specific anti-VEGFR2 therapy effect of sunitinib from other anti-angiogenic effects of a therapy (imatinib) that does not directly inhibit VEGFR2. Sunitinib, imatinib and placebo were administered daily for 11 d (264 h) to 45 BalbC mice bearing ectopic CT26 murine colorectal carcinomas. During the course of therapy, B-mode ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…This is in accordance with Zocco et al who applied CEUS with untargeted microbubbles to investigate patients with advanced hepatocellular carcinoma under sorafenib therapy in a clinical study, assessing parameters of microcirculation including AUC and observed a significant decrease of AUC following 15 days of sorafenib therapy, associated with a longer survival and with a significant correlation to progression free survival [33]. Differing from our study, Zocco et al applied a non-targeted intravascular ultrasound contrast agent, which, however, resembles BR55 in bubble size and kinetics providing similar measures of tumor microcirculation and a similar wash-in-phase of the MB uptake as non-targeted agents with intravascular kinetics and distribution to the same tumor regions [13,34,35]. …”
Section: Discussionmentioning
confidence: 88%
“…This is in accordance with Zocco et al who applied CEUS with untargeted microbubbles to investigate patients with advanced hepatocellular carcinoma under sorafenib therapy in a clinical study, assessing parameters of microcirculation including AUC and observed a significant decrease of AUC following 15 days of sorafenib therapy, associated with a longer survival and with a significant correlation to progression free survival [33]. Differing from our study, Zocco et al applied a non-targeted intravascular ultrasound contrast agent, which, however, resembles BR55 in bubble size and kinetics providing similar measures of tumor microcirculation and a similar wash-in-phase of the MB uptake as non-targeted agents with intravascular kinetics and distribution to the same tumor regions [13,34,35]. …”
Section: Discussionmentioning
confidence: 88%
“…The PA develops from E8.5-E10.5, in which PA3 forms by E9.5. Tbx1 is expressed in the PE at E8.5 and E9.5 (Payen et al, 2015;Zhang et al, 2005;Zhang et al, 2006). We used RNAscope in situ hybridization on coronal sections from embryos to determine if there is overlap between Foxi3 and Tbx1 mRNA expression in wild type embryos at E9.5 ( Figure 3A-3L).…”
Section: Inactivation Of Foxi3 In Endodermal Cell Lineages Causes Defmentioning
confidence: 99%
“…A particularly interesting technique is photoacoustic imaging due to the penetration depth of the ultrasound and optical absorption contrasts (Yao and Wang 2014). A non-exhaustive but representative panel of current techniques applied for in vivo tumor imaging is given in Table 1. In this imaging landscape, assessment of tumor angiogenesis via ultrasound is currently contingent on the use of contrast agent (Payen et al 2015) or very high frequencies (40 to 100MHz) (Ferrara et al 2000) because conventional ultrasound Doppler techniques suffer from a lack of sensitivity and from the impossibility to extract very slow blood flow (below 10 mm.s -1 ). The recently introduced Ultrafast Doppler technique (Bercoff et al 2011) can resolve both issues by increasing the sensitivity to blood motion detection by a factor 50 (Macé et al 2013) compared to conventional techniques and by enabling new paradigms for discrimination between tissue and blood signal using spatiotemporal information (Demené et al 2015).…”
Section: Introductionmentioning
confidence: 99%